Computer games for learning an evidence-based approach - Mayer, Richard E. (The MIT Press, 2014)
This book fills that need by providing a comprehensive and up-to-date investigation of what research shows about learning with computer games. The book is essential reading for researchers and students of educational games, instructional designers, learning-game developers, and anyone who wants to know what the research has to say about the educational effectiveness of computer games.